2001
DOI: 10.1590/s0066-782x2001000600003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of transesophageal echocardiography in patients with stroke without clinical evidence of cardiovascular sources of emboli

Abstract: Objective -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
(19 reference statements)
2
10
1
Order By: Relevance
“…We found seven similar published studies (Leung et al 1995; Warner and Momah 1996; Palazzuoli 2000; Cabral et al 2001; Tatani 2001; Ward 2006; Harloff 2006; Table 3). Only one of them was prospective (Harloff 2006), three included patients without a previous TTE (Warner and Momah 1996; Palazzuoli 2000; Tatani 2001), and two included patients with atrial fibrilation (Warner and Momah 1996; Harloff 2006).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found seven similar published studies (Leung et al 1995; Warner and Momah 1996; Palazzuoli 2000; Cabral et al 2001; Tatani 2001; Ward 2006; Harloff 2006; Table 3). Only one of them was prospective (Harloff 2006), three included patients without a previous TTE (Warner and Momah 1996; Palazzuoli 2000; Tatani 2001), and two included patients with atrial fibrilation (Warner and Momah 1996; Harloff 2006).…”
Section: Discussionsupporting
confidence: 74%
“…Only one of them was prospective (Harloff 2006), three included patients without a previous TTE (Warner and Momah 1996; Palazzuoli 2000; Tatani 2001), and two included patients with atrial fibrilation (Warner and Momah 1996; Harloff 2006). Only two of the studies specified the number of patients who had simultaneous patent foramen ovale and atrial septal aneurysm (Tatani 2001; Harloff 2006). This fact is relevant, since anticoagulation is considered beneficial only in patients with both these abnormalities (Mas et al 2001; Kizer et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This finding that echocardiography is associated with a change in management in 74% of stroke patients is higher than in previous reports, 7,14 most likely because the current study evaluated both the prescription of new anticoagulation and new cardiac medications, whereas previous research focused on anticoagulation only. By limiting the focus to anticoagulation, earlier studies often suggested that echocardiography is overused in stroke patients, because echocardiography is associated with a new prescription for anticoagulation in a minority of patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Only one of them was prospective (Harloff 2006), three included patients without a previous TTE (Warner and Momah 1996;Palazzuoli 2000;Tatani 2001), and two included patients with atrial fi brilation (Warner and Momah 1996;Harloff 2006). Only two of the studies specifi ed the number of patients who had simultaneous patent foramen ovale and atrial septal aneurysm (Tatani 2001;Harloff 2006). This fact is relevant, since anticoagulation is considered benefi cial only in patients with both these abnormalities (Mas et al 2001;Kizer et al 2005).…”
Section: Resultsmentioning
confidence: 99%